Identifikasi Komponen Minyak Atsiri Daun Kawista (Feronia limonia) dengan Metode Gas Cromatography-Mass Spectroscopy (GC-MS) - Saadatul Husna; St Chadijah; Aisyah Aisyah (Al-Kimia, 2013)
Indonesia has a vast variety of plants species which largely unexplored. Several researches have conducted to explore the potentials of the plants. However, the chemical constituents of Kawista plant have not been widely investigated. This study aimed to identify the components of the essential oil from Kawista leaves (Feronia limonia). This study consisted of two stages, namely the extraction of essential oil by distillation method and the analysis of the essential oil components by GC-MS method. The results showed that there are sixteen volatile components in the essential oil of Kawista leaves (Feronia limonia). They are 3-pentanol, 1-methyl siklopenatnol, 3methyl siklopentanol, 1,1-dimethyl 2-propenol, 4-tujanol, 2 methyl 3buten-2-ol, 1-(2-oksiranil etanon, 2-heksanon, 1-butanone cyclohexyl, 3-methyl 2 pentanon, 1-heksanal, 2-heksenal, 1-ethyl acetaldehyde, 2,5-tetrahidrodimethyl furan and γ-terpinen.